An evaluation of the effectiveness of the institutional mechanism to manage substance abuse in South Africa - Whiting, Sean Allen (2014)
Includes bibliographical references.This mixed method study of the effectiveness of the management of substance abuse in South Africa explored the way policies are formulated and implemented. A governance lens used coordination and public participation as indicators to measure the efficacy of the coordinating substance abuse structures (the Central Drug Authority, Provincial Substance Abuse Forums and Local Drug Action Committees) to implement the National Drug Master Plan 2006-2011. Coordinated governance, which include empowerment and resourcing of structures at the provincial and municipal levels will be helpful to provide necessary resources, expertise and skills to the "whole of society" for the implementation of future strategies